Occipital Headache Associated with C1 Hypoplasia - Kok, Selman; Gonen, Murat; Ergun, Ahmet Cemil; Kaplan, Metin (Turkish Neurological Soc, 2021)
[Abstract Not Available]
C1 hipoplazisi ile ilişkili oksipital baş ağrısı
Keywords: Atlas; hypoplasia; cervicogenic headache